Exploration Of Computational Thinking Skills Of Junior High School Student In Term Of FI And FD Cognitive Style - Hasanah, Merrina Uswatun; Masduki, Masduki (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
The purpose of this study is to investigate the computational thinking skills of junior high school students in terms of FI and FD cognitive styles on materials with numerical patterns. The type of research used is qualitative descriptive. The subjects of the study were 57 students from class VIII at one of the public junior high schools in Jepara. The data collection instruments used are computational thinking test questions, GEFT tests, and interviews. Researchers adopted three questions from the Pusmendik Kemdikbud class VIII to test students' computational thinking skills. All questions were validated by three mathematics education experts and tested on 5 grade VIII students before being used. In this study, four components of computational thinking: abstraction, pattern recognition, algorithmic thinking, and generalization were used to analyze students' computational thinking skills. This study focused on exploratory examination of pupils’ computational thinking with high categories, researchers selected 3 students on FI cognitive style and 2 students on FD cognitive style. The results showed that students with a FI cognitive style were able to meet all indicators of computational thinking namely abstraction, pattern recognition, algorithmic thinking, and decomposition. In contrast, students with FD cognitive styles are able to meet three indicators of computational thinking: abstraction, pattern recognition and generalization. Thus, it may be said that the ability to think computationally is related to the cognitive style of students.